2020
DOI: 10.1371/journal.pone.0235509
|View full text |Cite
|
Sign up to set email alerts
|

The first nationwide study on facing and solving ethical dilemmas among healthcare professionals in Slovenia

Abstract: Background Healthcare professionals (HCPs), patients and families are often faced with ethical dilemmas. The role of healthcare ethics committees (HECs) is to offer support in these situations. Aim The primary objective was to study how often HCPs encounter ethical dilemmas. The secondary objective was to identify the main types of ethical dilemmas encountered and how HCPs solve them. Subjects and methods We conducted a cross-sectional, survey-based study among HCPs in 14 Slovenian hospitals. A questionnaire w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…However, this study also reveals that Polish physicians are less likely to face or admit facing tough clinical decisions than their peers from the United States and western or northern European countries. Slightly above three quarters of our respondents (76.6%) reported confronting tough clinical decisions, whereas in similar studies with US physicians practicing general internal medicine, hematology/oncology, or critical care/pulmonary medicine (DuVal et al, 2004), general practitioners from Great Britain, Italy, Norway, and Switzerland (Hurst et al, 2007) and physicians from Croatia and Slovenia (Grosek at al. 2020;Grosek et al, 2021), almost all surveyed doctors (90% or above) reported having such an experience.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…However, this study also reveals that Polish physicians are less likely to face or admit facing tough clinical decisions than their peers from the United States and western or northern European countries. Slightly above three quarters of our respondents (76.6%) reported confronting tough clinical decisions, whereas in similar studies with US physicians practicing general internal medicine, hematology/oncology, or critical care/pulmonary medicine (DuVal et al, 2004), general practitioners from Great Britain, Italy, Norway, and Switzerland (Hurst et al, 2007) and physicians from Croatia and Slovenia (Grosek at al. 2020;Grosek et al, 2021), almost all surveyed doctors (90% or above) reported having such an experience.…”
Section: Discussionmentioning
confidence: 62%
“…Grosek et al, 2021 ). In a Slovenian study, ethical dilemmas associated with “long waiting periods for diagnostic and therapeutic treatment” and/or “allocation of limited resources” were indicated by 69.7% and 37.3% of the surveyed physicians, respectively (Grosek et al, 2020 ). However, only 20% of U.S. doctors indicated allocation as a source of ethical problems (Hurst et al, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 With the advent of new innovations in medicine a variety of ethical issues are faced by healthcare professionals in different settings involving their own personal values, the values of the institution, and the ethical, legal, and cultural values of society. 8 It has been seen through research those various ethical problems arising in different regions of the world need handling in different ways. When problems faced by Native Americans were analyzed it was found that due to the influence of various ethnic origins and isolation from the U.S. and trauma faced by them in history during colonization; competent healthcare providers were needed to deal with their specific issues.…”
Section: Reviewmentioning
confidence: 99%
“…Studies have been carried out in the healthcare area, although limited to medicine and nursing, that have highlighted the importance of giving professionals in medicine and nursing strategies for analysing and resolving ethical dilemmas that allow them to anticipate and reduce stress in their work (Corley, Minick, Elswick, & Jacobs, 2005;Førde & Aasland, 2008;Häggström, Mbusa, & Wadensten, 2008;Hofmeyer, 2003;Rathert, May, & Chung, 2016;Rushton, Kaszniak, & Halifax, 2013;Wadensten, Wenneberg, Silén, Tang, & Ahlström, 2008), but nothing specific to strategies for analysing and resolving them specifically (Barlow, Hargreaves, & Gillibrad, 2008;Bolin et al, 2008;Grosek et al, 2020;Kanofsky, 2020).…”
Section: Introductionmentioning
confidence: 99%